2014
DOI: 10.1177/0897190014562384
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists Role in Cholesterol Management

Abstract: Cholesterol management is an important factor in the modification of primary and secondary cardiovascular events. Guidelines emphasize incorporation of appropriate medication therapy and lifestyle adjustments to reduce low-density lipoprotein cholesterol (LDL-C) for cardiovascular disease (CVD) risk reduction. Of note, studies and nation-wide statistics indicate many patients do not achieve their LDL-C goals. Eliminating barriers and challenges associated with cholesterol management will allow patients to reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Pharmacists are integral members of the healthcare team, and their inclusion in management of chronic disease therapy has demonstrated their benefits in helping patients to achieve therapeutic goals in chronic disease states, such as hypertension, hyperlipidemia, diabetes and chronic obstructive pulmonary disease. 5 , 6 , 7 , 8 , 9 In the underserved population, pharmacists as part of a multidisciplinary team have helped homeless patients with diabetes, hypertension, and/or hyperlipidemia achieve therapeutic goals, identify medication-related problems, and provide cost-savings. 10 , 11 , 12 A report of a collaboration between a college of pharmacy and a community center that serves the homeless, uninsured and underinsured population showed that this academic-community partnership led to high satisfaction with the clinic providers and staff regarding pharmacy services, as well as improved quality of medication use.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists are integral members of the healthcare team, and their inclusion in management of chronic disease therapy has demonstrated their benefits in helping patients to achieve therapeutic goals in chronic disease states, such as hypertension, hyperlipidemia, diabetes and chronic obstructive pulmonary disease. 5 , 6 , 7 , 8 , 9 In the underserved population, pharmacists as part of a multidisciplinary team have helped homeless patients with diabetes, hypertension, and/or hyperlipidemia achieve therapeutic goals, identify medication-related problems, and provide cost-savings. 10 , 11 , 12 A report of a collaboration between a college of pharmacy and a community center that serves the homeless, uninsured and underinsured population showed that this academic-community partnership led to high satisfaction with the clinic providers and staff regarding pharmacy services, as well as improved quality of medication use.…”
Section: Introductionmentioning
confidence: 99%